Enhancing Local Community Welfare through the Resilience of Marine Ecotourism Micro, Small, and Medium Enterprises (MSMEs) in the Likupang Special Economic Zone, North Minahasa Regency - Agnes Lutherani Ch P Lapian; Een Novritha Walewangko; Yunita Mandagie (SOSIOEDUKASI, 2025)
Marine ecotourism has the potential to enhance local community well-being, but crises such as the COVID-19 pandemic have tested the sustainability of these benefits, particularly for Micro, Small, and Medium Enterprises (MSMEs). This study analyses the relationship between the development of marine ecotourism in the Likupang Special Economic Zone and the socio-economic well-being of local communities, with MSME resilience as a mediating variable. Cross-sectional survey data (n = 240) were analysed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that marine ecotourism in Likupang contributes positively to local community well-being. The tourism–marine economic and socio-cultural marine economic dimensions have a significant direct effect on well-being, whereas the environmental marine economic dimension does not directly improve well-being without operating through enhanced MSME resilience. All dimensions of marine ecotourism significantly strengthen the resilience of local MSMEs, which in turn drives improvements in community well-being. In other words, MSME resilience partially mediates the relationship between marine ecotourism and community well-being for economic and socio-cultural effects, and fully mediates this relationship for environmental effects. These findings confirm that the resilience of local MSMEs is a key factor that bridges the economic and environmental potential of ecotourism and its translation into tangible well-being for communities. In practical terms, sustainable tourism development strategies need to be accompanied by empowerment programmes and resilience-strengthening initiatives for MSMEs so that the benefits of marine ecotourism can be optimally experienced by local communities.